The dependence of shugoshin on Bub1-kinase activity is dispensable for the maintenance of spindle assembly checkpoint response in Cryptococcus neoformans. - Satya Dev Polisetty; Krishna Bhat; Kuladeep Das; Ivan Clark; Kevin G Hardwick; Kaustuv Sanyal (PLoS Genetics)
During chromosome segregation, the spindle assembly checkpoint (SAC) detects errors in kinetochore-microtubule attachments. Timely activation and maintenance of the SAC until defects are corrected is essential for genome stability. Here, we show that shugoshin (Sgo1), a conserved tension-sensing protein, ensures the maintenance of SAC signals in response to unattached kinetochores during mitosis in a basidiomycete budding yeast Cryptococcus neoformans. Sgo1 maintains optimum levels of Aurora B kinase Ipl1 and protein phosphatase 1 (PP1) at kinetochores. The absence of Sgo1 results in the loss of Aurora BIpl1 with a concomitant increase in PP1 levels at kinetochores. This leads to a premature reduction in the kinetochore-bound Bub1 levels and early termination of the SAC signals. Intriguingly, the kinase function of Bub1 is dispensable for shugoshin's subcellular localization. Sgo1 is predominantly localized to spindle pole bodies (SPBs) and along the mitotic spindle with a minor pool at kinetochores. In the absence of proper kinetochore-microtubule attachments, Sgo1 reinforces the Aurora B kinaseIpl1-PP1 phosphatase balance, which is critical for prolonged maintenance of the SAC response.